2008
DOI: 10.1007/s10295-007-0290-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of xylanase in Aspergillus phoenicis: a physiological and molecular approach

Abstract: Microbial xylanolytic enzymes have a promising biotechnological potential, and are extensively applied in industries. In this study, induction of xylanolytic activity was examined in Aspergillus phoenicis. Xylanase activity induced by xylan, xylose or beta-methylxyloside was predominantly extracellular (93-97%). Addition of 1% glucose to media supplemented with xylan or xylose repressed xylanase production. Glucose repression was alleviated by addition of cAMP or dibutyryl-cAMP. These physiological observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Xylanases production by A. phoenicis was shown positively affected by xylan, xylose and b -methylxyloside, similarly to the cases of other fungi belonging to the Aspergillus genus such as Aspergillus sydowii and A. tubingensis , as studied and discussed by Rizzatti et al [164]. This study also demonstrated that the levels of production of xylanase by A. phoenics , decreased when glucose was added to the inducers xylan or xylose, similarly to A. sydowii whose xylanase production is inhibited by glucose [165].…”
Section: Regulation Of Production Of Cellulases and Hemicellulases Inmentioning
confidence: 81%
“…Xylanases production by A. phoenicis was shown positively affected by xylan, xylose and b -methylxyloside, similarly to the cases of other fungi belonging to the Aspergillus genus such as Aspergillus sydowii and A. tubingensis , as studied and discussed by Rizzatti et al [164]. This study also demonstrated that the levels of production of xylanase by A. phoenics , decreased when glucose was added to the inducers xylan or xylose, similarly to A. sydowii whose xylanase production is inhibited by glucose [165].…”
Section: Regulation Of Production Of Cellulases and Hemicellulases Inmentioning
confidence: 81%
“…Interestingly, Herrera-Herrera et al [ 50 ] showed that in Cellulomonas flavigena , an actinobacteria with special interest for its ability to degrade cellulose and hemicellulose, addition of exogenous cAMP in repressor culture medium decreased catabolite repression, while supplementation enhanced cellobiohydrolase production. Similarly, Rizzati et al [ 51 ] showed in Aspergillus phoenicis that repression of xylanase expression by glucose was partially reversed by addition of cAMP or dbcAMP.…”
Section: Discussionmentioning
confidence: 93%
“…Aspergillus phoenicis, a thermotolerant fungus, has successfully been used in our laboratory to produce various enzymes with biotechnological applications [11,12]. This fungus was previously isolated from sugar cane bagasse and it has demonstrated high xylanase and b-xylosidase yields, as reported.…”
Section: Introductionmentioning
confidence: 95%